Syncope due to acute rheumatic fever with pacemaker-like syndrome - Bağrul, Denizhan (The Turkish Journal of Pediatrics, 2019)
The prolongation in the PR interval on the electrocardiogram is one of the minor criteria of Jones. Abnormal increases in the PR interval lead to hemodynamic impairments caused by atrioventricular asynchrony and is called pseudo-pacemaker or pacemaker-like syndrome in the literature. A 13-yearold boy who had polyarthralgia for six weeks was referred to the emergency room because of syncope while exerting effort. In the electrocardiography, the P wave was regularly seen at the onset of the T wave immediately after the QRS wave with extremely prolonged PR interval and mild tachycardia. Also, 24 hours rhythm Holter recording showed atrioventricular dissociation. The echocardiography revealed findings of severe carditis. Diagnosis of acute rheumatic fever accompanying pacemaker-like syndrome was made. Although the recommendation for marked first-degree atrioventricular block that causes hemodynamic impairment is pacemaker implantation, a significant improvement in the PR prolongation was observed in the short term with anti-inflammatory treatment because the impairment of conduction in the patient was due to inflammation. The pacemaker-like syndrome in a child is being reported for the first time in the literature.
Keywords: acute rheumatic fever; atrioventricular dissociation; cardiac conduction system; pacemaker-like syndrome